Prognosis of programmed ventricular stimulation in adult patients with syncope of unexplained origin: A historical cohort - Bruno Schaaf Finkler; Roberto Sant'Anna; Javier Pinos; Danilo Barros Zanotta; Thiago Camargo Moreira; Felipe Della Barba deJesus; Pedro Dutra Batista; Helena Guedes daRocha; Barbara Adelmann deLima; Marco Aurélio Lumertz Saffi; Gustavo Glotz deLima; Marcelo Kruse; et al. (Journal of Arrhythmia)
Abstract Background Programmed ventricular stimulation (PVS) during electrophysiological study (EPS), is a globally accepted tool for risk stratification of sudden cardiac death (SCD) in some specific clinical situations. The aim of this study was to evaluate the prognosis of ventricular arrhythmia induction in a cohort of patients with syncope of undetermined origin (SUO). Methods This is a historical cohort study in a population of patients with SUO referred for EPS between the years 2008–2021. In this interval, 575 patients underwent the procedure. Results Patients with induced ventricular arrhythmias had a higher occurrence of structural heart disease (36.7% vs. 76.5%), ischemic heart disease (28.2 vs. 57.1%), heart failure (15.5% vs. 34.4%), and lower left ventricular ejection fraction (59.16% vs. 47.51%), when compared to the outcome with a negative study. PVS triggered ventricular arrhythmias in 98 patients, 62 monomorphic and 36 polymorphic. During a median follow‐up of 37.6 months, 100 deaths occurred. Only the induction of sustained ventricular arrhythmias showed a significant association with the primary outcome (all‐cause mortality) with a p value <.001. After the performance of EPS, 142 patients underwent cardioverter‐defibrillator (ICD) implantation. At study follow‐up, 30 patients had therapies by the device. Only the induction of sustained monomorphic ventricular arrhythmia showed statistically significant association with appropriate therapies by the device (p = .012). Conclusion In patients with SUO, the induction of sustained monomorphic ventricular arrhythmia after programmed ventricular pacing is related to a worse prognosis, with a higher incidence of mortality and appropriate therapies by the ICD.